Novel Application of Steroid Eluting Stent in Petrous Apex Cholesterol Granuloma - Choi, Kevin J.; Jang, David W.; Zomorodi, Ali R.; Codd, Patrick J.; Friedman, Allan; Abi Hachem, Ralph (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study describes the safety and efficacy of mometasone furoate eluting stents in the management of petrous apex cholesterol granuloma approached through an endonasal endoscopic route and assesses the restenosis rate.Methods Consecutive patients undergoing endoscopic endonasal marsupialization of a petrous apex cholesterol granuloma at a tertiary referral center who had a mometasone furoate eluting stent placed intraoperatively were reviewed in a retrospective fashion. Postoperative endoscopy was used to determine success of surgery and stenting.Results Five patients were included in the study, three were primary cases and two patients had revision surgeries performed. The steroid eluting stent was placed successfully and safely in all patients with no dural or vascular injuries. The average follow-up duration was 10.6 months. There was no restenosis in three patients and one patient had an immediate restenosis that was debrided in clinic (revision case). This was patent at the 16 months follow-up. One patient also developed stenosis, 4 months after surgery due to sphenoid sinusitis.Conclusion Mometasone furoate eluting stents are safe and effective in the primary management of petrous apex cholesterol granuloma. Further studies are needed to assess their efficacy in revision cases and for long term results.
Keywords: cholesterol granuloma; steroid eluting stents; surgical techniques; endoscopic skull base surgery